ANALISA KANDUNGAN GIZI TEPUNG KACANG GUDE HITAM (Cajanus cajan) DENGAN BEBERAPA PERLAKUAN PENDAHULUAN - Gelora H Augustyn; Erynola Moniharapon; Sani Resimere (Universitas Pattimura, 2017)
This study was aimed to determine the nutrient content of the black pigeon pea flour that has been subjected to several pre-treatments. A completely randomized experimental design was applied in this study that consisted of four levels of treatments replicated 3 times. The results showed that either moisture, protein, fat, carbohydrate, or fiber content were significantly influenced by pre-treatments on processing of the black pigeon pea flour. However, the ash content was not significantly affected. The best result was obtained by A2 treatment that produced the black pigeon pea flour with the moisture, ash, protein, fat, carbohydrate and fiber contents of 6.16%, 0.94%, 24.32%, 2.94%, 65.64%, and 3.21%, respectively.